Estimating profit shifting in South Africa using firm-level tax returns - Hayley Reynolds; Ludvig Wier (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
Using the universe of South African corporate tax returns for 2009-14, we estimate profit- and debt-shifting responses in South Africa. We find evidence that South African subsidiaries engage in profit shifting and that profit-shifting responses to tax incentives across all channels are systematically higher compared to developed countries.
Keywords: H25; H26; H87; O23; 330; developing countries; international taxation; multinational firms; profit shifting; tax